Reimagining Participatory Agile Development in Community-Industry Partnerships - Liang, Calvin A.; Tseng, Emily; Fetterolf, Elizabeth; Gray, Mary L. (CHI 2026, 2026)
Computing’s ubiquity and accumulation of capital have positioned modern tech giants to be key players in society’s responses to crises. Fulfilling this potential, however, requires methods and incentives for the industry to meaningfully support communities (“community-industry partnerships”). This paper examines one such partnership: an effort to co-develop software with and for community health workers that began in 2020 with the COVID-19 pandemic. Our multi-year, ethnographic work explores how Agile development, the industry’s standard development practice, delimits the possibilities of community participation. Analyzing the project’s breakdowns, we find stakeholders aligned on goals but misaligned on three key tensions: whose expertise takes primacy, how disagreements are surfaced, and how accountability is enacted. We propose reimagining these tensions as guiding principles for stronger partnerships: yielding to community expertise, embracing disagreement as productive friction, and ensuring accountability through realignment. Our framework offers guidance for community-industry partnerships to enhance societal resilience, in crises and beyond.